Penguatan Daya Saing UMKM Gula Aren melalui Inovasi Teknologi Tepat Guna Penepung Gula Semut - Nurhayani, Ulfa; Herliani, Rini; Mursid, Mursid; Nurwendari, Weny; Sitompul, Haryani Pratiwi; Sibarani, Choms Choms Gary Ganda Tua; Purba, Erny Luxy; Silalahi, Sondang Aida (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the capacity of palm sugar artisan groups in Teluk Bakung Village in terms of production, quality, marketing, and business management as an effort to strengthen the competitiveness of palm sugar–based MSMEs. The program was implemented using a participatory approach that included stages of socialization, training, mentoring, and evaluation. Evaluation instruments consisted of observation sheets to assess technical skills and comprehension questionnaires to measure managerial understanding, which were analyzed using descriptive comparative methods. The results indicate a significant increase in daily production capacity through the adoption of appropriate technology in the form of a grinding machine. Product quality also improved, as evidenced by finer and more hygienic physical characteristics, along with the establishment of the “Arentapure” brand identity. In addition, partners successfully expanded their market reach through social media and began implementing simple financial record-keeping systems separate from household finances. These findings demonstrate that the program is effective in transforming traditional enterprises into more professional business units with strong potential for long-term economic sustainability.